Dari Revolusi Hijau ke Food Estate: Kapitalisme Pedesaan dan Warisan Dualisme Ekonomi dalam Sejarah Pembangunan Pertanian Indonesia - Tirto Adhie Soerjo; Sari Oktafiana (Jurnal Sejarah Indonesia, 2026)
This article examines the long-term impacts of Indonesia's Green Revolution during the New Order era on the rural socio-economic structure, particularly in Java. Using a political-economic historical approach and data from the 1983 and 2023 Agricultural Censuses, the study argues that the Green Revolution did not merely modernize agriculture through technology and chemical inputs but also reshaped rural society through class differentiation, patronage relations, and agrarian commodification. The policy fostered a persistent economic dualism between large landowners and land-poor farmers. This historical trajectory continues in the present, especially under President Joko Widodo's Food Estate program and its anticipated expansion under President-elect Prabowo Subianto, both of which reproduce a top-down, capital-intensive, and exclusionary development model. The findings highlight that without structural agrarian reform and agricultural policy, Indonesia risks remaining trapped in agricultural involution, an intensification of labor without corresponding improvements in productivity or welfare, and recurring food security crises.